Dilemas e tensões da supervisão escolar paulistana - Torres, Amanda Coelho (2022)
In school supervision in São Paulo, where I have been working since 2017, it is possible to observe dilemmas and tensions that generate discomfort. These are revealed in the dialogues between school supervisors, which point to the lack of identity of the position, work overload, anxiety, confusion of priorities, which were already present before the pandemic and intensified with it. But these questions are not mine alone; many colleagues report this in our conversations and even in work meetings. As a result, the question that arises for this research is: How to overcome the malaise in school supervision and build an emancipated and emancipatory supervisory action? The hypothesis that I present is that the daily routine of school supervision in São Paulo is marked by dilemmas and tensions that can generate discomfort, and that can be understood and overcome from the analysis of the social, political and cultural context in which supervision is inserted; the identification of existing contradictions in the exercise of supervisory action and the characterization of supervisors' discomfort to propose a training process that can develop an emancipated and emancipating supervisory action. The general objective is to understand the São Paulo school supervision in its attributions and practices, towards a quality public education. And the specific objectives are: to analyze the social, political and cultural context in which São Paulo school supervision is inserted; identify existing contradictions in the exercise of supervisory action; to characterize the discomforts in São Paulo school supervision and to propose a training process that helps in overcoming the discomfort and aims to build an emancipated and emancipatory supervision in the city of São Paulo. The theoretical framework will be composed of related studies by authors who think about school supervision in São Paulo and by the Critical Theory of the Frankfurt School, especially Theodor Adorno, in addition to other contemporary thinkers. The research was bibliographical and documental and the methodology of the empirical research was the oral history of thematic life, where the speech analysis of five scalar supervisors with different times of experience in São Paulo school supervision was carried out. Participants, highlighting the following categories in the analysis: Expectations, formation and adaptation; The malaise; Pandemic; and In search of emancipation. As research results, we confirm our hypothesis that São Paulo school supervisors experience dilemmas and tensions that can generate discomfort, but that there is also room for emancipation in school supervision that can be permeated by moments of study, critical reflection, awareness, articulation between the pairs.